ANALISIS STRATEGI PERANG TOYOTOMI HIDEYOSHI UNTUK MEMPERSATUKAN JEPANG DALAM NOVEL THE SWORDLESS SAMURAI KARYA KITAMI MASAO - Kadek Apriliani; Dian Pramita Sugiarti (SPHOTA: Jurnal Linguistik dan Sastra, 2017)
ABSTRACT This article entitled “Analysis of Toyotomi Hideyoshi’s War Strategy to Unite Japan Depicted in the Novel The Swordless Samurai by Kitami Masao” is mainly aimed at revealing Toyotomi Hideyoshi’s war strategy to unite Japan. This research was based on some books concerning The Swordless Samurai’s novel. The data was collected by reading those books for obtaining information relating to the war strategy and policy used for uniting Japan. The data was analyzed by descriptive qualitative method. Two theories were used in analyzing the data, namely the theory of war strategy psychology and the theory of Hegemony. The results of the analysis shows that the war strategy of Toyotomi Hideyoshi to unite Japan in the novel The Swordless Samurai are approach techniques with enemies, techniques to trick enemies and improve welfare for troops of war. These three techniques Toyotomi Hideyoshi able to unite Japan with a short time. Keywords: Toyotomi Hideyoshi, War Strategy, Policy